التحدِّيات التي يواجهها طلبة الكلية الجامعية الإسلامية العالمية بسلانجور في تعلّم اللغة العربية لأغراض سياحية : دراسة ميدانية - Nurul Husna Roslan
Arabic for Tourism Purpose in Kolej Universiti Sains Islam Antarabangsa Selangor(KUIS) is a compulsory subject for students on degree level for specialization in Arabic as a Second Language. This study discusses the challenges and the reasons faced by Arabic course‟s students while studying the Arabic for Tourism Purpose in KUIS. For this study, the method used by the author is qualitative method by conducting a semi-structured interview. Interview was conducted on 19 students fron the Academy of Islam Centre (AI) in KUIS who took the Arabic for Tourism Purpose subject. Groups of respondents were devided into 3 groups consisting of 6-7 students. Process of information gathering and research data were analyzed using the program ATLAS.ti software version 7.1.7. And the study found that factors that lead the challenges of students in study Arabic for Tourism Purpose is the internal and external factors. The internal factors consist of the factors from the student their selves. While the external factors consist of the curriculum syllabus factor, the friends factor, as well as environmental factor. At the end of the research, the researcher suggests that the students need to change their thought about the difficulty of Arabic language and they also have to take part in co-curricular activities, in addition of strengthen the curriculum syllabus of Arabic for Tourism Purpose.